Perioperative and oncologic outcomes of robotic surgery for pediatric solid abdominal tumors: a single-center 10-year experience - Pokharkar, Ashitosh; Yadav, Priyank; Kandpal, Deepak K.; Mahajan, Amita; Chowdhary, Sujit Kumar (Frontiers in Pediatrics, 2025)
IntroductionMinimally invasive surgery (MIS) has revolutionized oncological surgery with benefits such as smaller incisions and quicker recovery. However, its use in pediatric population is debated due to concerns about complete tumor resection and complications. Robotic surgery, offering enhanced visualization and precision, may address these issues. This study reviews a decade of robotic surgery for pediatric solid abdominal tumors at a single center, assessing perioperative and oncological outcomes.MethodsThis prospective, single-arm study involved patients aged over six months, treated between 2013 and 2023 for solid abdominal tumors. Exclusion criteria included weight <6 kg, distant metastasis, and tumors >6 cm in shortest diameter. All patients underwent thorough preoperative assessment, including imaging and multidisciplinary evaluation. Surgeries were performed using the da Vinci Si Surgical System and data on patient demographics, perioperative outcomes, and follow-up were systematically collected.ResultsThe study cohort included 20 patients (9 boys and 11 girls) with a median age of 3.5 years. The median operative time was 114 min, with a median hospital stay of 3 days. Conversion to open surgery was necessary in 10% of cases. R0 resection was achieved in all cases, with a satisfactory lymph node sampling. Median follow-up of 5 years showed overall survival and event-free survival rates of 90%.ConclusionRobotic surgery for pediatric abdominal tumors is safe and effective, reducing blood loss and hospital stays without compromising oncological outcomes. Proper case selection and adherence to oncological principles are essential. Further multicenter studies are needed to validate these findings and optimize the use of robotic surgery in pediatric oncology.